Diversity, distribution, ethnobotany, and taxonomic revision of the genus Senegalia (Fabaceae) in Thailand - PRATEEP PANYADEE; RODRIGO DUNO DE STEFANO; CHARAN LEERATIWONG; SAKUNTALA NINKAEW; WITSANU SAISORN; JIRATTHI SATTHAPHORN; NATCHA SUTJARITJAI; HENRIK BALSLEV (Society for Indonesian Biodiversity, 2026)
Abstract. Panyadee P, De Stefano RD, Leeratiwong C, Ninkaew S, Saisorn W, Satthaphorn J, Sutjaritjai N, Balslev H. 2026. Diversity, distribution, ethnobotany, and taxonomic revision of the genus Senegalia (Fabaceae) in Thailand. Biodiversitas 27 (2): d270236. https://doi.org/10.13057/biodiv/d270236. Senegalia (Fabaceae) represents the most diverse group of armed legumes in Thailand and has not been taxonomically revised since Nielsen’s (1985) treatment under Acacia. Here, we present the first comprehensive taxonomic revision of Senegalia in Thailand, integrating morphological and ethnobotanical evidence in accordance with current generic concepts. Field surveys and extensive herbarium studies revealed 14 species comprising 16 taxa, belonging to two sections, sect. Senegalia and sect. Monacanthea. Two taxa (Senegalia catechu and Senegalia pennata subsp. pennata) are introduced and now naturalized, while 13 species are native to the country. Senegalia pennata subsp. insuavis, previously regarded as exotic, is confirmed as native based on its occurrence in undisturbed habitats, whereas S. pruinescens is excluded due to misidentification. Species richness is highest in northern and peninsular Thailand. Six taxa (five species) have documented ethnobotanical uses, including food, medicine, dyes, and fish poison. Vegetative characters, particularly petiole gland morphology, leaflet venation, and stipule form prove reliable for field identification and are emphasized to facilitate practical use. This revision presents an updated taxonomic framework and serves as a reference for botanical, ethnobotanical, and conservation studies of Senegalia in Thailand.